Results of mechanochemical synthesis of methylene blue complex with d-metals - Kadirova, M; Sabirov, V (Scientific and Technical Journal of Namangan Institute of Engineering and Technology, 2024)
The article describes the mechanochemical synthesis of a complex based on methylene blue (MB) and cobalt(II) chloride and a description of the structure of the complex. The synthesis of the complexes was carried out by the mechanochemical method by mixing the reagents in a stoichiometric ratio in an agate mortar until a homogeneous mass was formed. Dimethylformamide (DMF) was added dropwise to the resulting reaction mixture until a homogeneous dark blue solution was formed. The crystals required for X-ray diffraction analysis were obtained by slow evaporation of the reaction solution over a week. The parameters of the crystals were analyzed by the X-ray structure method.The mechanochemical synthesis of the complexes was carried out by mixing the raw materials in stoichiometric proportions by grinding them in an agate mortar. DMF was added dropwise to the reaction mixture until a homogeneous dark blue solution was formed. The crystals required for X-ray diffraction analysis were obtained by evaporating the solution at room temperature for a week. The reaction yield was 85%. The mechanochemical synthesis of the [MB]2[CoCl4] complex was proven based on X-ray diffraction analysis. The crystal required for X-ray diffraction determination of the structure was grown only from a DMF solution. It has been established that the synthesis of complexes based on transition metal chlorides and MB can be easily carried out using the mechanochemical method.